Quality of Life among Obstetric Fistula Patients at Kitovu Mission Hospital: A Health Facility-Based Cross-Sectional Study in Masaka District, Uganda - Samuel Kakembo; Christine Atuhairwe; Ivan Mugisha Taremwa (Hindawi Limited, 2020)
Background. Obstetric fistula (OF) remains a silent neglected maternal challenge associated with devastating life consequences. Living with OF presents far-reaching physical, social, psychosocial, and emotional concerns, which negatively impact a woman's quality of life. This study evaluated the quality of life among obstetric fistula patients in Masaka district, Uganda. Method. A cross-sectional study was conducted among 63 women diagnosed with OF at Kitovu Mission Hospital. Data were collected using a questionnaire, observation, in-depth interviews, and focus group discussions. Data were analyzed at univariate, bivariate, and multivariate levels, where the ordinal logistic regression model was applied. The qualitative data was transcribed and analyzed using qualitative content analysis. Results. Majority (87%) of the women diagnosed with OF reportedly had a poor quality of life. Bivariate analysis indicated that level of education (P<0.001), employment status (P<0.001), energy for everyday life (P<0.001), capacity to work (P<0.001), satisfaction with personal relationships (P<0.001), feelings of loneliness (P<0.001), negative feelings (P=0.002), and self-confidence (P<0.001) were significantly associated with good QoL. Multivariate analysis showed increased odds of good QoL increased among women with self-confidence (OR = 32.320; CI = 2.019-517.467), formal education (OR = 9.9497; CI = 1.075-92.048), women who did not experience difficulties in mobility (OR = 19.144; CI = 0.149-2456.770), and women who were satisfied with their personal relationships (OR = 5.785; CI = 0.447-74.824). Conclusion. A holistic fistula treatment approach is required that takes into consideration all aspects of life to address the consequences of obstetric fistula to realize improved quality of life among patients.